The Eucharist and the Spirituality of the Catholics in the Public Space - Mathias Jebaru Adon (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
This study aims to describe the spirituality of the Jewish liturgy in the celebration of the Eucharist and its impact on the involvement of Indonesian Catholics in the public sphere. This study was born from the concern that the Indonesian people are rich in spiritual values but are unable to shape a civilized public life. Therefore, this research awakens Catholics to be actively involved in the public sphere, especially in socio-political life, and to color it with gospel values. However, this call will be realized if the Eucharist as the source and peak of the Christian life can renew and encourage Catholics in Indonesia to take part in God's mission to save all people. So the Eucharist must draw on the spirituality contained in Jewish worship as the locus of a personal encounter with the God who saves. This study uses a literature study that finds cracks in the religious life and people's lives in public spaces because the celebration of the Eucharist is not able to renew the lives of Catholics witness in the world.